CRETACEOUS AND TRIASSIC SUBDUCTION-ACCRETION, HIGH-PRESSURE-LOW- TEMPERATURE METAMORPHISM, AND CONTINENTAL GROWTH IN THE CENTRAL PONTIDES, TURKEY - Okay A.I.; Tüysüz O.; Satir M.; Özkan-Altiner S.; Altiner D.; Sherlock S.; Eren R.H. (My University, 2006)
Biostratigraphic, isotopic, and petrologic data from the Central Pontides document major southward growth of the Eurasian continental crust by subduction-accretion during the Cretaceous and Triassic Periods. A major part of the accreted material is represented by a crustal slice, 75 km long and up to 11 km thick, consisting of metabasite, metaophiolite, and mica schist that represent underplated Tethyan oceanic crustal and mantle rocks. They were metamorphosed at 490 °C and 17 kbar in mid-Cretaceous time (ca. 105 Ma). The syn-subduction exhumation occurred in a thrust sheet bounded by a greenschist facies shear zone with a normal sense of movement at the top and a thrust fault at the base. A flexural foreland basin developed in front of the south-vergent high-pressure-low-temperature (HP-LT) metamorphic thrust sheet; the biostratigraphy of the foreland basin constrains the exhumation of the HP-LT rocks to the Turonian - Coniacian, ~20 m.y. after the HP-LT metamorphism, and ~25 m.y. before the terminal Paleocene continental collision. The Cretaceous subduction-accretion complex is tectonically overlain in the north by oceanic crustal rocks accreted to the southern margin of Eurasia during the latest Triassic-earliest Jurassic. The Triassic subduction-accretion complex is made up of metavolcanic rocks of ensimatic arc origin and has undergone a high pressure, greenschist facies metamorphism with growth of sodic amphibole. Most of the Central Pontides consists of accreted Phanerozoic oceanic crustal material, and hence is comparable to regions such as the Klamath Mountains in the northwestern United States or to the Altaids in Central Asia. © 2006 Geological Society of America.
Keywords: CONTINENTAL GROWTH; EXHUMATION; HP-LT METAMORPHISM; OROGENY; PONTIDES; TURKEY; Jurassic; Triassic; Eocene; Paleocene; Coniacian; Turonian; Mesozoic::Jurassic; Мезозой::Юрская; Mesozoic::Triassic; Мезозой::Триасовая; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен; Cenozoic::Paleogene::Paleocene; Кайнозой::Палеоген::Палеоцен; Mesozoic::Cretaceous::Upper::Coniacian; Мезозой::Меловая::Верхний::Коньякский; Mesozoic::Cretaceous::Upper::Turonian; Мезозой::Меловая::Верхний::Туронский